Treating Diabetic Foot Osteomyelitis: A Practical State-of-the-Art Update - Lipsky, Benjamin A. (Medicina (Kaunas), 2021)
Background and Objectives: Diabetic foot osteomyelitis (DFO) can be difficult to treat and securing optimal clinical outcomes requires a multidisciplinary approach involving a wide variety of medical, surgical and other health care professionals, as well as the patient. Results of studies conducted in the past few years have allowed experts to formulate guidelines that can improve clinical outcomes. Material and Methods: We conducted a narrative review of the literature on treat- ment of DFO, with an emphasis on studies published in the last two years, especially regarding antimicrobial therapies and surgical approached to treatment of DFO, supplemented by our own extensive clinical and research experience in this field. Results: Major amputations were once com- mon for DFO but, with improved diagnostic and surgical techniques, “conservative” surgery (foot- sparing, resecting only the infected and necrotic bone) is becoming commonplace, especially for forefoot infections. Traditional antibiotic therapy, which has been administered predominantly in- travenously and frequently for several months, can often be replaced by appropriately selected oral antibiotic regimens following only a brief (or even no) parenteral therapy, and given for no more than 6 weeks. Based on ongoing studies, the recommended duration of treatment may soon be even shorter, especially for cases in which a substantial portion of the infected bone has been resected. Using the results of cultures (preferably of bone specimens) and antimicrobial stewardship princi- ples allows clinicians to select evidence-based antibiotic regimens, often of a limited pathogen spec- trum. Intra-osseous antimicrobial and surgical approaches to treatment are also evolving in light of ongoing research. Conclusions: In this narrative, evidenced-based review, taking consideration of principles of antimicrobial stewardship and good surgical practice, we have highlighted the recent literature and offered practical, state-of-the-art advice on the antibiotic and surgical management of DFO.